Análisis de caudales mediante la transformada Wavelet con aplicación a la estimación de la producción de las centrales hidroeléctricas no regulables - Alemán Quimbiulco, Edy Franklin (2015)
The object of this work is to present a methodology for analyzing water flows from the use of Wavelet Transform, where the result of the analysis can allow to consider a different input data for planning in non-regulated hydroelectric plant. Was analyzed, some families with the mathematical model of Wavelet Transform to find the most appropriate statistical estimation model, which is used in some areas of planning power. A tool that allowed us to compare the decomposition of the data by type of selected family and, according to test data group, the appropriate level of decomposition was established. To determine the validity of the analysis, a comparison between the reference data of the flow of water from a hydroelectric plant in the country was made from data obtained in the analysis of Wavelet. Compared to other methods were employed in data analysis and estimation of energy production. We observed the behavior that each contributed in the decomposition process data to estimate the electrical energy from the change in input data.